2008
DOI: 10.3174/ajnr.a1380
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Basiocciput Development in CHARGE Syndrome

Abstract: BACKGROUND AND PURPOSE:The causative gene of the common congenital malformation referred to as CHARGE syndrome is CHD7. Affected individuals often undergo head and neck imaging to assess abnormalities of the olfactory structures, hypothalamus-pituitary axis, and inner ear. We encountered a few children with severe hypoplasia of the basiocciput during a radiologic assessment of patients with CHARGE syndrome. To our knowledge, this anomaly has not been reported. Our purpose was to evaluate the incidence and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…These skull base anomalies consisted of a J‐shaped sella and a dorsal angulation of the clivus. These findings confirm the findings of Fujita et al (2009) and are consistent with the preliminary results of a study in which we analyzed the clivus of 23 confirmed patients with CHARGE on MRI or CT scans. We found that the vast majority had an abnormal clivus (Figure 2) [yet unpublished data].…”
Section: Diagnostic Value Of Cranial Imagingsupporting
confidence: 93%
See 1 more Smart Citation
“…These skull base anomalies consisted of a J‐shaped sella and a dorsal angulation of the clivus. These findings confirm the findings of Fujita et al (2009) and are consistent with the preliminary results of a study in which we analyzed the clivus of 23 confirmed patients with CHARGE on MRI or CT scans. We found that the vast majority had an abnormal clivus (Figure 2) [yet unpublished data].…”
Section: Diagnostic Value Of Cranial Imagingsupporting
confidence: 93%
“…The guidelines we present here for cranial imaging in patients with CHARGE syndrome are based on previously published neuro‐radiologic recommendations (Asakura et al, 2008; Bergman, Janssen, et al, 2011b; Fujita et al, 2009; Gregory et al, 2013; Pinto et al, 2005; Vesseur, Free, et al, 2016a) in addition to current insights in detectable neuro‐radiologic abnormalities and anatomic variants in patients with CHARGE syndrome (see Table 3). …”
Section: Overview Of Guidelines and Recommendations From Literaturementioning
confidence: 99%
“…Basioccipital hypoplasia has also been reported to be common in CHARGE syndrome, with the CHD7 gene thought to have a role in neural crest development. 22 Two of the patients with CHARGE syndrome had an abnormal clivus, and all 3 had dysmorphic brain stems. The olfactory nerves, regional facial structures, and skull base are derived from the cranial neural crest, and the association may explain the incidence of facial and skull base abnormalities present in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we give an overview of all CHD7 missense variants reported in the literature before 15 June 2011 [Asakura et al, 2008;Bartels et al, 2010;Bergman et al, 2011a, b;Dauber et al, 2010;De Arriba Munoz et al, 2011;Delahaye et al, 2007;Felix et al, 2006;Feret et al, 2010;Fujita et al, 2009;Gao et al, 2007;Holak et al, 2008;Jongmans et al, 2006Jongmans et al, , 2008Jongmans et al, , 2009Kim et al, 2008;Lalani et al, 2006;Pauli et al, 2012;Vissers et al, 2004;Vuorela et al, 2007;Wessels et al, 2010;Wincent et al, 2008] and the variants that were reported in the NCBI Single Nucleotide Polymorphism database (http://www.ncbi.nlm.nih.gov/SNP, dbSNP build 132) with frequency data (n = 104, Supp. Table S1).…”
Section: Inclusion Of Chd7 Missense Variantsmentioning
confidence: 99%